Fermented weed juice as catalyzer on growth and yield of Luffa acutangula / Mohamad Amir Shah Yusop …[et al.] - Yusop, Mohamad Amir Shah; Mohammed, Anisah; Zaini, Mohd Waliyudin; Abdul Aziz, Noorshilawati; Abdullah, Nur Suraya; Rosli, Fazidah; Muhamad Ridzwan, Hendrie Johann (2013)
Weed was commonly described as unwanted plant. It was a highly successful wild plant. adapted to rapidly colonies bare ground or land that constantly being disturbed Weeds may give the benefit effects if it was converted to natural fertilizer such as Fermented Weed Juice. The application of fermented weed juice in natural farming system can reduce the application of chemical fertilizer in agriculture and at the same time reduced the unwanted plant in the field The objectives of this study were to identify the best types and rate of Fermented Weed Juice on growth and yield of Luffa acutangula. This study was conducted at 100 Acre. UiTM Jengka. Pahang from May 2012 until January 2013. The study was carried out by using Randomize Completely Block Design with 13 treatments andfour replications. The treatments consist of three types of weed that were Amaranthus spinonsus. Chromolena odorata. and Asystasia gangetica with 10ml. 20ml, 30ml and 40ml of fermented weed juice applied as foliar fertilizer. Data collected were analyzed by using MINITAB and Microsoft Excel to compare the each treatment. Asystasia gangetica with 30 ml give the best effect to the height, number of leaves and number of fruits of Luffa acutangula. From this study it can be concluded that Asystasia gangetica with 30 ml was the best treatment among the others.